Measurement of Methanol and Ethanol Contents in Most Commonly Used Herbal Distillates Produced by Three Famous Brands - Mahdi YOUSEFI; Reza AFSHARI; Masoumeh SADEGHI; Roshanak SALARI (Tehran University of Medical Sciences, 2018)
Background: Herbal distillates have been used for many centuries as herbal medicines in Traditional Persian medicine. The main purpose of this study was to determine methanol and ethanol contents in commonly-used industrial herbal distillates produced by three famous factories in Khorasan Razavi, Mashhad, Iran (2014-2015). Methods: Ninety herbal waters of ten types of most commonly used herbal distillates including Willow (Salix alba), Ajava seeds (Carum copticum), Fennel (Foeniculum vulgare), Poleigamander (Teucrium polium), Forty plants, Peppermint (Mentha piperita), Camel thorn (Alhagi camelorum), Chicory (Cichorium intybus), Fumitory (Fumaria officinalis) and Rose water (Rosa damascene) of three famous company in Mashhad were randomly bought from market. Methanol and ethanol contents of each sample were measured by Gas chromatography according to the standard method. Collected data were analyzed by SPSS using appropriate descriptive statistical tests. Results: The highest average amount of methanol of all tested distillates is for forty plants (46.06 mg/dl) and M. piperita (46.72 mg/dl) and the lowest for ajava seed (8.46 mg/dl). The maximum and minimum ethanol level was reported for rose water (0.39 mg/dl) and ajava seed (0.15 mg/dl), respectively. Conclusion: High methanol and ethanol concentrations may induce toxicity in people taking these products regularly for a long time. Therefore, considering the harmful effects of methanol and ethanol on human health, further studies are required for determining permitted levels of methanol and ethanol in herbal distillates.